Student engagement: Gender differences in senior high school - Rismawati, Rismawati; Ikromi, Ziyadi Ali; Hidayat, Novi (Privietlab, 2025)
Student engagement is a broad concept that encompasses student commitment, interaction, and connection with academic material, curriculum, and activities that support learning and achievement. Student engagement has been conceptualized as a three-dimensional construct: emotional/affective, behavioral, and cognitive engagement. There are differences in student engagement levels between male and female students, based on PISA results between 2012 and 2022, with performance in mathematics declining among male students, but remaining stable among female students in Indonesia. This study aimed to identify gender-based differences in student engagement. This research method employed a quantitative approach. Sampling was conducted using non-probability and purposive sampling (N=467). Confirmatory Factor Analysis (CFA) was used to test the construct validity of each variable using the Lisrel 8.8 software, and difference tests were conducted using SPSS 23 software. The results of the study indicate that there were differences in variance between male and female groups in the behavioral and cognitive engagement variables, while there were no differences in variance between male and female groups in the emotional engagement variable. Additionally, the categorization of scores for the behavioral engagement, emotional engagement, and cognitive engagement variables was dominated by the moderate category. Future research should investigate variables related to behavioral and cognitive engagement among female students to foster school engagement. This study aims to develop potential teaching strategies and interventions for both male and female students to enhance student engagement in school.